Nilai Pendidikan Moderasi Beragama Materi Khutbah Jum’at Perspektif Peserta Lomba Khutbah MTQ Korpri V Tingkat Nasional di Kendari - Akhmad Shunhaji; Ahmad Zain Sarnoto; EE Junaedi Sastramiharja (Journal on Education, 2023)
This study examines the value of religious moderation education on Friday sermon material from the perspective of participants in the national level MTQ Korpri V sermon competition in Kendari. Moderation exists in religious teachings, because all aspects of life are regulated in religion, including human attitudes and behavior which are part of morality. In addition to existing in religious teachings, moderation in general also exists outside of religious attitudes, such as in political, economic, social attitudes. culture and so on. Because moderation as an attitude and perspective does not exist in anything unless it will make something beautiful, flexible, and easy to accept, because it is more in line with human nature. The findings of this study are; 1. Materials on Religious Moderation in Friday Khutbah Takwa Testament, 2. Moderation Education Materials in Religious Moderation Materials in Friday Khutbahs. This study uses a qualitative narrative approach